Does extensive on-water rowing increase muscular strength and endurance? - Lawton, T. W.; Cronin, J. W.; McGuigan, M. R. (Journal of Sports Sciences, 2012)
The purpose of this study was to compare changes in aerobic condition, strength, and muscular endurance following 8 weeks of endurance rowing alone or in combination with weight-training. Twenty-two elite rowers were assigned to (1) rowing (n = 10, 250-270 km · week-1) or (2) rowing (n = 12, 190-210 km/week) plus four weight-training sessions each week. Pre and post mean and standardized effect-size (ES) differences in aerobic condition (watts at 4 mmol/L) and strength (isometric pull, N), prone bench-pull (6-repetition maximum, 6-RM), 5- and 30-repetition leg-press and 60-repetition seated-arm-pull (J, performed on a dynamometer) normalized by body mass and log-transformed were analysed, after adjusting for gender. The standardized differences between groups were trivial for aerobic condition (ES [±90% CI] = 0.15; ±0.28, P = 0.37) and prone bench-pull (ES = 0.27; ±0.33, P = 0.18), although a moderate positive benefit in favour of rowing only was observed for the seated-arm-pull (ES = 0.42; ±0.4, P = 0.08). Only the weight-training group improved isometric pull (12.4 ± 8.9%, P < 0.01), 5-repetition (4.0 ± 5.7%, P < 0.01) and 30-repetition (2.4 ± 5.4%, P < 0.01) leg-press. In conclusion, while gains in aerobic condition and upper-body strength were comparable to extensive endurance rowing, weight-training led to moderately greater lower-body muscular-endurance and strength gains.